1929
DOI: 10.3181/00379727-27-4573
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Digestion by Organisms from the Termite Gut

Abstract: The termite thrives in an environment which is most unusual and which requires specialized adaptation for survival. Its galleries are largely cellulose as also is its diet. Relatively little combined nitrogen is found in its food other than that derived from consumption of fecal materials of its fellows. That sector of the nitrogen cycle which includes the metabolism of the termite is as yet unexplored.It is probable that the energ)-requirements of the termite are derived from the destruction of cellulose. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1933
1933
1994
1994

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Cellulose digestion is also found in other insect groups such as the Thysanura, Orthoptera, Coleoptera and Hymenoptera. [3,4,23,[87][88][89][90][91][92]). The extent of cellulose digestion in wood was found to be between 59% and 99% [84][85][86], resulting in the production of lower fatty acids, mainly acetic acid, and CO 2 and H 2 [39,82].…”
Section: Degradation Of Cellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose digestion is also found in other insect groups such as the Thysanura, Orthoptera, Coleoptera and Hymenoptera. [3,4,23,[87][88][89][90][91][92]). The extent of cellulose digestion in wood was found to be between 59% and 99% [84][85][86], resulting in the production of lower fatty acids, mainly acetic acid, and CO 2 and H 2 [39,82].…”
Section: Degradation Of Cellulosementioning
confidence: 99%
“…Already since the 1920s several authors demonstrated the breakdown of cellulose by termites (e.g. [3,4,23,[87][88][89][90][91][92]).…”
Section: Degradation Of Cellulosementioning
confidence: 99%
“…Dickman (1931) found many different cellulose digesting organisms in the nest walls but not in the intestinal contents of Reticulitermesflavipes. Beckwith & Rose (1929) reported cellulose digestion by bacteria isolated from Reticulitermes hesperus and several other species. These workers incubated their cultures aerobically as was done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases where positive results were obtained the bacteria were not identified and no attempt was made to count them. The digestion of cellu10s~ by the isolated bacteria was a slow process requiring days or even months to be achieved (Beckwith and Rose 1929;Hungate 1946b;Mannesmann 1972;Krelinova et al 1977b) and in the case of the isolates obtained by Beckwith and Rose (1929) and Mannesmann (1?72), growth of the organisms on cellulose was better under aerobic than under anaerobic conditions. The removal of the gut bacteria from Nasutitermes exitiosus and Coptotermes lacteus by feeding tetracycline, had little effect on the cellulase activity of whole termites, indicating that bacteria play little part in cellulose digestion in these termites (O'Brien et al 1979).…”
Section: Role Of Gut Bacteriamentioning
confidence: 99%